2020
DOI: 10.1001/jamadermatol.2020.1287
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoscopic Evaluation of Central Centrifugal Cicatricial Alopecia Beyond the Vertex Scalp

Abstract: Central centrifugal cicatricial alopecia (CCCA) is a scarring alopecia commonly seen in African American individuals. 1 It classically affects the vertex scalp, although 1 study 2 suggests that it may manifest as patchy hair loss beyond the vertex. In that study, the histopathologic, dermatoscopic, and clinical findings were crucial in diagnosis. However, another study 3 reported histopathologic changes in the vertex scalp consistent with CCCA even without clinically visible hair loss. Our study explored derma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In addition, like SD, CCCA is associated with scaling. Follicular scales were found to be a classic dermoscopic finding in majority of the CCCA patients (68%) in a cross-sectional study [26], while SD is associated with interfollicular and perifollicular scales [27]. There have also been several case reports of patients with long-standing scalp psoriasis, another inflammatory and pruritic papulosquamous dermatosis of the scalp, that progressed to cicatricial alopecia [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, like SD, CCCA is associated with scaling. Follicular scales were found to be a classic dermoscopic finding in majority of the CCCA patients (68%) in a cross-sectional study [26], while SD is associated with interfollicular and perifollicular scales [27]. There have also been several case reports of patients with long-standing scalp psoriasis, another inflammatory and pruritic papulosquamous dermatosis of the scalp, that progressed to cicatricial alopecia [28].…”
Section: Discussionmentioning
confidence: 99%
“…In the authors' experience, clinical progression of hair loss is often variable, as some patients experience rapid progression to end‐stage disease within a few years of disease onset while others may experience slow, gradual progression over decades and may never approach end‐stage or extensive involvement. Though a recent study found that clinically unaffected areas of the scalp in CCCA patients have histologic evidence of active disease, 6 variation in disease course, particularly in the rate of disease progression, is unexplained by this discovery and instead suggests multiple CCCA disease phenotypes. We therefore sought to characterize the expression pattern in a small subset of CCCA patients with accelerated progression to clinically severe, extensive disease involvement.…”
Section: Introductionmentioning
confidence: 88%